Multi-drug resistant Staphylococcus aureus isolated from broiler chickens at poultry farms in Kota Bharu, Kelantan. - Erkihun Aklilu; Tang Siew Ching; Abd Rahman Aziz; Tan Ching Giap; Mohd Mokhtar Arshad; Kalthum Hashim; Jasni Sabri; Nur Hardy Abu Daud; Aung Tun Khaing; Basripuzi Nurul Hayyan Hassan Basri (2013)
Antimicrobial resistant bacteria have been of a seroius public health concern for decades. Despite the continuous efforts to control and prevent antimicrobial resistance, some species of bacteria remained problematic and were proved to update their antimicrobial resistance profile from time to time. the emergence and spread of multi-drug resistance Staphylococcus aureus (S.aureus)in food animals has been attributed to the irrational use of antimicrobials in commercial animal productions, Hence, the presence and increasing reports of multi-drug resistant bacterial pathogens from food animals poses potential public health risk. In this study, cloacal swab samples were collected from 60 chickens and 50 environmental samples in the premises of two farms in Kota Bharu, Kelantan. Isolation and identification using selective media, Brilliance MRSA2 agar and results from antimicrobial sensitivity tests revealed that 13.33% (8/60) and 12%(6/50) of the samples from cloacal swabs and environemental surfaces respectively, were methicillin-resistant S.aureus (MRSA). This finding is important and possibly implies the risks of transmission and spread of MRSA to human through handling of contaminated poultry meat. Futher investigation is, however, required to access the degree of possible risks of transmissions of the bacteria from chicken meat to humans and vice versa.